Gradac in Potirna on the island of Korčula (In situ, 2025)
The paper presents the results of archaeological research at Gradac hillfort in Potirna, located on the southwestern part of the island of Korčula. The research was conducted in April 2024, as part of a student research project funded by the Department of Archaeology of the University of Zadar. The archaeological material found has enabled at least a partial understanding of the everyday life of the Bronze Age community on this southern Dalmatian island.
Keywords: hillfort; Gradac; Korčula; Bronze Age